Method for manufacturing aluminium nitride single crystal, and aluminium nitride single crystal

JP2025031600AActive Publication Date: 2025-03-07TOHOKU UNIV +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024131035
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-08-23
Filing Date
2024-08-07
Publication Date
2025-03-07
Estimated Expiration
2044-08-07

AI Technical Summary

Benefits of technology

【0019】 本発明によれば、結晶成長速度が大きくて厚い窒化アルミニウム単結晶を製造することができると共に、サファイア基板からの剥離が容易で、透明な窒化アルミニウム単結晶を簡易に提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025031600000001_ABST
    Figure 2025031600000001_ABST
Patent Text Reader

Abstract

To simply provide a transparent and thick aluminium nitride single crystal capable of manufacturing the aluminium nitride single crystal having a large crystal growth rate and easily peeled from a sapphire substrate.SOLUTION: A method for manufacturing an aluminium nitride single crystal comprises steps of: preparing a raw material melt obtained by melting Al and N in the saturation state of aluminium nitride at a predetermined temperature in an alloy melt; and growing an aluminium nitride single crystal on the AlN layer side of an AlN template substrate by bringing the AlN template substrate into contact with the raw material melt to cool at least the periphery of the AlN template substrate to a temperature lower than the predetermined temperature. The AlN layer of the AlN template substrate has a half value width of 300 arcsec or less in the X-ray rocking curve of the (10-12) plane of a C plane AlN single crystal.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing an aluminum nitride single crystal, and an aluminum nitride single crystal. [Background technology]

[0002] Ultraviolet light-emitting devices are next-generation light sources that are expected to be used in a wide range of applications, such as sterilization light sources, high-brightness white light sources combined with phosphors, high-density information recording light sources, resin curing light sources, etc. These ultraviolet light-emitting devices are made of AlGaN-based nitride semiconductors.

[0003] Candidates for substrate materials for this AlGaN-based nitride semiconductor include SiC, GaN, and AlN (aluminum nitride) due to their high lattice matching with AlGaN. However, SiC and GaN absorb light with energies greater than 380 nm and 365 nm, respectively, limiting the wavelength range that can be extracted. On the other hand, AlN has a wider band gap than AlGaN and is not limited in wavelength range like SiC and GaN, so it is considered to be the best substrate material for ultraviolet light-emitting devices. However, AlN exhibits high dissociation pressure at high temperatures, so it does not become molten under normal pressure. For this reason, it is extremely difficult to produce AlN single crystals from their own melt, as is the case with silicon single crystals.

[0004] Thus, in the past, attempts have been made to produce bulk AlN single crystals by using the sublimation method to produce crystals (for example, see Non-Patent Document 1). However, in the method of producing AlN crystals using the sublimation method, a high temperature exceeding 2448K is required in the source section, which poses the problem that it is difficult to produce crystals that can withstand practical use in terms of size and cost.

[0005] To solve this problem, the present inventors have developed a liquid phase growth method for AlN single crystals, in which a N-containing gas is brought into contact with the surface of an Al-containing alloy melt to grow a crystal on the surface of the melt, as a method for obtaining inexpensive, high-quality aluminum nitride (AlN) crystals at low temperature and normal pressure (see, for example, Patent Document 1). This method does not use a template substrate, and therefore can also prevent the occurrence of threading dislocations, misfit dislocations, and distortion in the grown AlN crystal.

[0006] Furthermore, in order to increase the growth rate of AlN single crystals, the inventors have developed an AlN single crystal growth method which includes a heating step in which a Ni-Al alloy melt is brought into contact with a sintered body containing AlN, such as a crucible for holding the melt, and heated to a temperature at which AlN becomes thermodynamically unstable in the alloy melt, thereby dissolving a portion of the AlN sintered body into the melt, and a crystallization step in which, after the heating step, the alloy melt is cooled to a thermodynamically stable temperature, thereby crystallizing AlN crystals in the alloy melt (see, for example, Patent Document 2).

[0007] Furthermore, the inventors have also developed an AlN single crystal growth method that allows for continuous production of AlN single crystals without the need for heating and crystallization steps by creating a temperature gradient in a Ni-Al alloy melt, holding an AlN sintered body in the high-temperature part, and crystallizing AlN crystals in the low-temperature part (see, for example, Non-Patent Document 2).

[0008] The linear and quadratic interaction coefficients of Al, N, and Cr in Fe melt and Fe-Cr alloy melt are disclosed as a function of temperature (see, for example, Non-Patent Documents 3 and 4). Also, the equilibrium constant of the reaction producing AlN in Fe melt is disclosed as a function of temperature (see, for example, Non-Patent Documents 3 or 5). [Prior art documents] [Non-patent literature]

[0009] [Non-Patent Document 1] Carsten Hartmann et. al., “Preparation of Bulk AlN Seeds by Spontaneous Nucleation of Freestanding Crystals”, Jpn. J. Appl. Phys., 2013, 52, 08JA06 [Non-Patent Document 2] Rintaro Miyata, Makoto Otsuka, Masayoshi Adachi, Hiroyuki Fukuyama, "AlN growth on AlN / sapphire template substrate using Ni-Al melt", Proceedings of the 170th Annual Meeting of the Japan Institute of Metals, Spring 2022, [Retrieved February 9, 2023], Internet〈URL:https: / / confit.atlas.jp / guide / event / jim2022spring / subject / 2ISIJ107-12-03 / advanced〉 [Non-Patent Document 3] Wan-Yi KIM, et. al., “Thermodynamics of Aluminum, Nitrogen and AlN formation in Liquid Iron”, ISIJ International, 2007, Vol.47, No.7, p.945-954 [Non-Patent Document 4] Jong-Oh JO, et. al., “Thermodynamic Interaction between Chromium and Aluminum in Liquid Fe-Cr Alloys Containing 26 mass% Cr”, ISIJ International, 2011, Vol. 51, No.2, p.208-213 [Non-Patent Document 5] Mitsutaka Hino and Kimihisa Ito, “THERMODYNAMIC DATA FOR STEELMAKING”, Tohoku University Press, 2010 [Patent documents]

[0010] [Patent Document 1] JP 2019-194133 A [Patent Document 2] JP 2022-37713 A Summary of the Invention [Problem to be solved by the invention]

[0011] The liquid phase growth method for aluminum nitride single crystals described in Patent Documents 1 and 2 can produce very good quality aluminum nitride single crystals at low cost, but the crystal growth rate is somewhat slow. Furthermore, aluminum nitride single crystals produced by HVPE method, sublimation method, etc., which can be used as seed crystals, are expensive and colored. When coloration is observed with the naked eye, the transmittance of deep ultraviolet light tends to be low. For example, an aluminum nitride single crystal that is amber colored has an absorption coefficient α of 50 cm at a wavelength of 265 nm. -1 In ultraviolet light-emitting devices using such aluminum nitride single crystals, there is a risk of reduced luminous efficiency when light is emitted from the substrate side.

[0012] The present invention has been made in light of these problems, and has an object to easily provide a transparent aluminum nitride single crystal that can be produced with a high crystal growth rate and is thick, and that can be easily peeled off from a sapphire substrate. [Means for solving the problem]

[0013] (1) preparing a raw material melt by dissolving Al and N in an aluminum nitride saturated state in an alloy melt containing at least one element selected from the group consisting of Fe, Ni, and Co, and at least one element selected from the group consisting of Mn, Cr, V, Ti, Te, Mo, Nb, Zr, Re, W, Ta, and Hf, at a predetermined temperature; bringing an AlN template substrate, comprising a sapphire substrate having an AlN layer formed on its surface, into contact with the raw material melt and cooling at least the periphery of the AlN template substrate to a temperature lower than the predetermined temperature, thereby growing an aluminum nitride single crystal on the AlN layer side of the AlN template substrate; The AlN layer of the AlN template substrate has an X-ray rocking curve half-width of 300 arcsec or less for the (10-12) plane of a C-plane AlN single crystal, a void is formed between the sapphire substrate and the aluminum nitride single crystal after the aluminum nitride single crystal is grown.

[0014] (2) The method for producing an aluminum nitride single crystal according to (1), wherein the alloy melt is an Fe-Cr alloy melt or an Fe-Cr-Ni alloy melt.

[0015] (3) The method for producing an aluminum nitride single crystal according to (1) or (2), further comprising the step of peeling off the aluminum nitride single crystal from the sapphire substrate after growing the aluminum nitride single crystal.

[0016] (4) The method for producing an aluminum nitride single crystal according to any one of (1) to (3), comprising: preparing the raw material melt by contacting a substance containing aluminum nitride with the alloy melt and holding the predetermined temperature for a predetermined time so that Al and N dissolve from the substance into the alloy melt and aluminum nitride is saturated at the predetermined temperature; and then contacting the AlN template substrate with the raw material melt.

[0017] (5) An aluminum nitride single crystal formed on an AlN template substrate having an AlN layer formed on a surface of a sapphire substrate, The AlN layer of the AlN template substrate has an X-ray rocking curve half-width of 300 arcsec or less for the (10-12) plane of a C-plane AlN single crystal, a gap is formed between the sapphire substrate and the aluminum nitride single crystal, At least one element selected from the group consisting of Fe, Ni, and Co, An aluminum nitride single crystal containing at least one of Mn, Cr, V, Ti, Te, Mo, Nb, Zr, Re, W, Ta and Hf as an impurity element.

[0018] (6) An aluminum nitride single crystal formed on an AlN template substrate having an AlN layer formed on a surface of a sapphire substrate, The AlN layer of the AlN template substrate has a threading dislocation density of 1×10 9 / cm 2 is as follows: a gap is formed between the sapphire substrate and the aluminum nitride single crystal, At least one element selected from the group consisting of Fe, Ni, and Co, An aluminum nitride single crystal containing at least one of Mn, Cr, V, Ti, Te, Mo, Nb, Zr, Re, W, Ta and Hf as an impurity element. Effect of the Invention

[0019] According to the present invention, it is possible to produce a thick aluminum nitride single crystal having a high crystal growth rate, and it is also possible to easily provide a transparent aluminum nitride single crystal which can be easily peeled off from a sapphire substrate. [Brief description of the drawings]

[0020] [Figure 1A] FIG. 1 is a graph for explaining a method for producing an aluminum nitride single crystal according to the present invention, which shows the relationship between the amount of dissolved Al and the amount of dissolved N at various temperatures in a melt of Fe-16 mass% Cr. [Figure 1B] 1B is a schematic diagram for explaining the states (1) and (2) in FIG. 1A. FIG. [Diagram 2] 1 is a front view showing one embodiment of the overall configuration of an aluminum nitride single crystal growing apparatus applicable to a manufacturing method of an aluminum nitride single crystal according to the present invention. FIG. [Diagram 3] 2 is a cross-sectional SEM image of an AlN template substrate after growing an aluminum nitride single crystal in Example 1. [Figure 4] 11 is a cross-sectional SEM image of an AlN template substrate after growing an aluminum nitride single crystal in Example 2. [Diagram 5] 13 is a cross-sectional SEM image of an AlN template substrate after growing an aluminum nitride single crystal in Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] (Method of manufacturing aluminum nitride single crystal) Hereinafter, an embodiment of the present invention will be described with reference to the drawings and examples. In a method for producing an aluminum nitride single crystal according to one embodiment of the present invention, an aluminum nitride (AlN) single crystal can be produced through a step of preparing a raw material melt and a step of growing an aluminum nitride single crystal as described below.

[0022] <Process for preparing raw material melt> That is, first, in an atmosphere containing nitrogen, an alloy melt consisting of at least one element selected from Fe, Ni, and Co, and at least one element selected from Mn, Cr, V, Ti, Te, Mo, Nb, Zr, Re, W, Ta, and Hf is prepared in a container such as a crucible. An alloy raw material may be put into the crucible and heated to form an alloy melt, or a metal raw material may be put into the crucible and heated to form an alloy melt in the crucible. The alloy constituting the alloy melt does not contain other elements except for unavoidable impurities. In addition, in the stage of the raw material before dissolving Al and before heating, the alloy does not contain Al, except in the case where it is an unavoidable impurity. Note that Mn, Cr, V, Ti, Te, Mo, Nb, Zr, Re, W, Ta, and Hf are elements that increase the solubility product of Al and N. It is particularly preferable to select at least one element selected from Cr and Nb as the element that increases the solubility product of Al and N. Then, Al and N are dissolved in this alloy melt at a predetermined temperature in a saturated state of aluminum nitride (AlN) to prepare a raw material melt.

[0023] The amounts of dissolved Al and dissolved N will be specifically described using an Fe-16mass%Cr alloy melt as a specific example. Figures 1A and 1B are a graph and a schematic diagram showing the relationship between the amounts of dissolved Al and dissolved N at various temperatures in an Fe-16mass%Cr alloy melt, and the amounts of dissolved Al and dissolved N are points on the equilibrium concentration curves at a given temperature as shown in Figure 1A. In the graph of Figure 1A and the schematic diagram of Figure 1B, (1) indicates the process of adjusting the raw material melt, and (2) indicates the process of growing an aluminum nitride single crystal. The alloy melt is preferably composed mainly of at least one element selected from Fe, Ni, and Co, and contains at least one of these elements in an amount of 50 mass% or more.

[0024] Here, the above-mentioned predetermined temperature may be a temperature at which Al and N dissolve at their saturated solubility according to the curve shown in FIG. 1A at a predetermined pressure of nitrogen to be supplied so as to form a raw material melt, and is preferably equal to or higher than the melting point of the alloy constituting the alloy melt used, and is preferably lower than 2448K, which is the temperature in the sublimation method. By raising the temperature to a predetermined temperature as shown by the arrow to (1) in FIG. 1A, Al and N dissolve in the alloy melt to the saturated state of aluminum nitride. The pressure of the nitrogen to be supplied is arbitrary, but is preferably 0.1 to 1 bar, and can be, for example, 1 bar.

[0025] 1A and 1B will now be described in more detail. The reaction by which AlN is produced from Al and N dissolved in the raw material melt is represented by the following formula (1). Al + N → AlN(s) (1)

[0026] In addition, the equilibrium constant K of the reaction in equation (1) is expressed by the following equation (2) because the activity of AlN is considered to be 1.

number

[0027] where f Al and f N are the activity coefficients of Al and N in at least one of the elements Fe, Ni, and Co based on 1 mass% (mass%), and [mass%Al] and [mass%N] are the mass percent concentrations (dissolved amounts) of Al and N in the raw material melt. If the raw material melt contains at least one of the elements Fe, Ni, and Co, Al, and N, as well as one or more elements X that increase the solubility product of Al and N, then f Al and f N are expressed by the following equations (3) and (4), respectively.

[0028]

number

[0029] Here, e i j is the first-order interaction coefficient of component j on component i, and r i j,k is the quadratic interaction coefficient of component j and component k on component i. For example, the interaction coefficients in equations (3) and (4) when the raw material melt is composed of Fe, Al, N, and Cr and the element X is Cr are shown as a function of temperature in Non-Patent Documents 3 and 4. Using these values, f Al and f N can be sought.

[0030] The equilibrium constant K in equation (2) is also shown as a function of temperature in Non-Patent Documents 3 and 5. Al and f N By substituting into equation (2), the product (solubility product) of the amount of dissolved Al [mass%Al] and the amount of dissolved N [mass%N] at each temperature can be obtained. For example, Figure 1A shows the equilibrium concentration relationship between Al and N determined from the solubility product of Al and N at various temperatures in an Fe-16mass%Cr alloy melt. As shown in Figure 1A, it can be seen that the solubility product of Al and N decreases as the temperature of the raw material melt decreases.

[0031] The alloy melt in this embodiment is preferably an Fe-Cr alloy melt or an Fe-Cr-Ni alloy melt. Commercially available stainless steel (such as SUS304 or SUS430) may be used as the raw material for the alloy melt. In the case of an Fe-Cr alloy melt, it is preferable that the Fe is 50% by mass or more and 90% by mass or less, the Cr is 10% by mass or more and 50% by mass or less, and the predetermined temperature is within a range of 1773K to 2073K. In the case of an Fe-Cr-Ni alloy melt, it is preferable that the Fe is 50% by mass or more and 90% by mass or less, the Cr and the Ni are 10% by mass or more and 50% by mass or less in total, the value of the Cr content / (the Cr content+the Ni content) is greater than 0 and less than 1 on a mass basis, and the predetermined temperature is within a range of 1673K to 2073K. It is preferable that the alloy melt contains a large amount of elements that increase the AlN solubility product ([mass%Al][mass%N]). Therefore, the Cr content is preferably 16% by mass or more and 50% by mass or less, and more preferably 18% by mass or more and 50% by mass or less.

[0032] The predetermined temperature is preferably 1773K or more and 1973K or less, more preferably 1773K or more and 1873K or less, in both cases of Fe-Cr alloy melt and Fe-Cr-Ni alloy melt. Although it depends on the nitrogen partial pressure, if the temperature of the alloy melt is 1873K or less at 1 bar of nitrogen, it is possible to prevent the aluminum nitride of the AlN template substrate waiting on the alloy melt from undergoing changes such as partial decomposition. In addition, it is preferable to increase the temperature range (temperature width ΔT for crystal growth) for cooling while growing crystals between the predetermined temperature, which is higher than the melting point of the alloy melt for dissolving Al and N in the alloy melt, and the temperature at which the alloy melt starts to solidify (freezing point), because this allows the crystal growth time to be longer. For example, it is preferable to set the temperature width ΔT for crystal growth to 50K or more, more preferably 100K or more. To achieve this, depending on the above-mentioned predetermined temperature, for example, the melting point (freezing point) of the alloy constituting the alloy melt is preferably 1773K or lower, and more preferably 1723K or lower.

[0033] In an alloy melt consisting of at least one element selected from among Fe, Ni, and Co, and at least one element selected from among Mn, Cr, V, Ti, Te, Mo, Nb, Zr, Re, W, Ta, and Hf, in order to increase the AlN solubility product while lowering the melting point of the alloy compared to the above-mentioned Fe-Cr alloy melt, it is preferable to use, for example, an Fe-Cr-Ni alloy melt (a ternary alloy melt of Fe, Cr, and Ni). Alternatively, a Ni-Cr alloy melt, a Co-Cr-Mo alloy melt, or the like may be appropriately selected.

[0034] In this case, a method for dissolving Al and N from the alloy melt to prepare the raw material melt may be, for example, to bring a substance such as a sintered body containing aluminum nitride into contact with the alloy melt placed in a container and hold it in this state at a predetermined temperature for a predetermined time. As a result, Al and N dissolve from the substance such as the sintered body into the alloy melt to a saturated state of AlN, thereby preparing the raw material melt. Note that the substance brought into contact with the alloy melt is not limited to a sintered body containing aluminum nitride, and may be any substance, such as a crystal containing aluminum nitride, that dissolves Al and N in the alloy melt.

[0035] As another method for preparing the raw material melt, Al may be supplied from a crucible containing the alloy melt into the alloy melt, and a sintered body containing Al may be used as the crucible. For example, it is preferable to use an aluminum nitride crucible or an alumina crucible. For example, the alloy melt is placed in a crucible made of an aluminum nitride sintered body, and in that state, it is held at a predetermined temperature for a predetermined time. As a result, Al and N are dissolved in the alloy melt from the crucible to become saturated with AlN, and the raw material melt can be prepared. Note that the alloy melt may be placed in the crucible after it is prepared, or the alloy raw material may be placed in the crucible and heated to form the alloy melt in the crucible. Also, the crucible may be a sintered body containing Al, and a sintered body or crystal piece containing aluminum nitride may be placed in the crucible as a raw material for aluminum nitride single crystal as described above. When using a crucible that does not contain N, such as an alumina crucible, it is preferable to put a sintered body or crystal pieces containing aluminum nitride as a raw material for the aluminum nitride single crystal, or to separately supply N from an atmospheric gas or the like.

[0036] The state where Al and N in the alloy melt reach the saturated solubility of AlN at a predetermined temperature is called the raw material melt. After preparing the raw material melt, a seed crystal is brought into contact with the raw material melt in an atmosphere containing nitrogen, and at least the periphery of the seed crystal is cooled to a temperature lower than a predetermined temperature. As a method for lowering the temperature at least around the seed crystal to a temperature lower than a predetermined temperature, the seed crystal may be cooled by controlling the temperature of a member supporting the seed crystal, or a part or the whole of the raw material melt may be cooled to a temperature lower than a predetermined temperature by controlling the temperature of a heater, or these cooling methods may be combined. As a result, the temperature of the raw material melt near the seed crystal or the temperature of the whole raw material melt decreases, and the solubility product of Al and N in the raw material melt in the cooled range decreases, for example, as shown by the arrow (2) in the graph of FIG. 1A. Since Al and N dissolved in the raw material melt in a saturated state of AlN become supersaturated by the difference due to this decrease in solubility product, an aluminum nitride single crystal can be precipitated on the surface of the seed crystal. In this way, an aluminum nitride single crystal can be grown by the precipitation of an aluminum nitride single crystal.

[0037] The cooling rate after the seed crystal is brought into contact with the raw material melt is optional and can be adjusted, for example, in the range of 0.1 K / min to 10 K / min. The thickness and flatness of the resulting crystal can be adjusted by the above-mentioned predetermined temperature, the temperature range ΔT for crystal growth, and the cooling rate.

[0038] <Step of growing aluminum nitride single crystal> In the method for producing an aluminum nitride single crystal according to the embodiment of the present invention, the seed crystal is maintained at a temperature lower than the predetermined temperature of the raw material melt, or the raw material melt as a whole is continuously cooled so that the state in which Al and N are supersaturated is continued, thereby continuously growing the aluminum nitride single crystal. The seed crystal used in this growth process is an AlN template substrate. As is generally known, the AlN template substrate is a sapphire substrate having an AlN layer formed on the surface thereof. In this specification, the AlN layer of the single crystal in the AlN template substrate is simply referred to as an AlN layer. In the present invention, an aluminum nitride single crystal is grown on the AlN template substrate (on the AlN layer of the AlN template substrate), so that a gap is formed between the sapphire substrate and the aluminum nitride single crystal to be grown after the aluminum nitride single crystal is grown. In the present invention, the raw material melt in the cooled range is made supersaturated with Al and N to promote the precipitation of the aluminum nitride single crystal. Therefore, compared with the case where the crystal is grown only on the surface of the melt or the case where a temperature gradient is provided in the alloy melt containing Al, the present invention allows the aluminum nitride single crystal to grow at a high growth rate. Furthermore, at the interface between the sapphire substrate where oxygen diffusion from sapphire (Al2O3) occurs and the aluminum nitride single crystal, the components of the alloy melt are included as impurities and diffuse. Furthermore, the aluminum nitride single crystal becomes thicker, and stress is concentrated at the interface. It is believed that these phenomena cause the interface between the AlN layer of the AlN template substrate and the sapphire substrate to peel off, causing voids at the interface. It is believed that this peeling occurs during the cooling process after the aluminum nitride single crystal is grown. The average thickness of the aluminum nitride single crystal to be grown is preferably 30 μm or more, more preferably 80 μm or more.

[0039] The AlN template substrate used in the present invention is an AlN template substrate in which a C-plane AlN layer is epitaxially grown on a C-plane sapphire substrate, and the half-width of the X-ray rocking curve of the (10-12) plane of the AlN layer is 300 arcsec or less. Furthermore, it is more preferable that the film thickness of the AlN layer on the sapphire substrate is 0.3 μm or more and 1.2 μm or less, and it is more preferable that the half-width of the X-ray rocking curve of the (0002) plane of the AlN layer is 150 arcsec or less. The X-ray rocking curve is measured by ω-scanning with an X-ray diffractometer (for example, D8 DISCOVER AUTOWAFS; manufactured by Bruker AXS). The detector side of the X-ray diffractometer is an open slit, and the aperture width of the detector is 0.5°.

[0040] In addition, the AlN template substrate used in the present invention has a threading dislocation density of 1×10 9 / cm 2 It is preferable that the value is less than 2×10 8 / cm 2 The threading dislocation density can be determined by counting the number of dark spots in a cross-sectional TEM image and calculating the density of the dark spots per unit area.

[0041] By using an AlN template substrate in which the half-width of the X-ray rocking curve of the (10-12) plane of the AlN layer grown on the sapphire substrate is 300 arcsec or less, the crystal quality of the AlN single crystal produced by the manufacturing method of the present invention can be improved. By using such an AlN template substrate, the half-width of the X-ray rocking curve of the (10-12) plane of the aluminum nitride single crystal formed on the AlN template substrate can be 450 arcsec or less. In addition, when the AlN template substrate is immersed in a raw material melt to grow an AlN single crystal in liquid phase, the AlN layer on the surface of the AlN template substrate can be prevented from being decomposed and lost due to etching. Note that when the AlN layer in contact with the raw material melt is polycrystalline, or even when it is single crystal, if the half-width of the X-ray rocking curve of the (10-12) plane is greater than 300 arcsec, the AlN layer is easily decomposed, and the AlN layer may disappear when immersed in the raw material melt.

[0042] In addition, the threading dislocation density from the cross-sectional TEM image was 1×10 9 / cm 2 By using the AlN template substrate described below, it is possible to prevent threading dislocations, misfit dislocations, and distortion from occurring in the grown AlN crystal.

[0043] The sapphire substrate used for the AlN template substrate preferably has a C-plane that is inclined at an off angle of 0.05° or more and 0.55° or less.

[0044] An AlN template substrate in which a C-plane AlN layer is epitaxially grown on a C-plane sapphire substrate and the half-width of the X-ray rocking curve of the (10-12) plane of the AlN layer is 300 arcsec or less can be manufactured by subjecting the AlN template substrate grown by MOCVD to a dislocation reduction treatment by annealing in a nitrogen atmosphere at 1823K or higher (for example, 1873K). The dislocation reduction treatment increases the amount of oxygen diffused from sapphire (Al2O3) to the AlN layer, and it is possible to have a high oxygen concentration region or an AlON layer at the interface.

[0045] The AlN layer is preferably grown by MOCVD using trimethylaluminum (TMA) and ammonia as source gases.

[0046] On the AlN template substrate, the AlN layer formed using the MOCVD method is transparent to the naked eye. Its transmittance in the deep ultraviolet region is also higher than that of seed crystals colored amber or other colors formed by other methods. For example, the absorption coefficient α at a wavelength of 265 nm is 30 cm -1 By using such an AlN template substrate as a seed crystal, the aluminum nitride single crystal formed on the AlN template substrate also tends to be transparent.

[0047] The method may further include a step of peeling off the aluminum nitride single crystal from the sapphire substrate after the aluminum nitride single crystal is grown. According to the present invention, since there is a gap between the sapphire substrate and the aluminum nitride single crystal, the peeling step is easier than when there is no gap. The peeling step may be performed by mechanically peeling the aluminum nitride single crystal by utilizing the gap, or by naturally peeling the aluminum nitride single crystal by adjusting the cooling rate during cooling to room temperature after the crystal is separated from the alloy melt after growth to enlarge the gap. By these methods, it is possible to obtain a transparent, self-supporting aluminum nitride single crystal.

[0048] (Aluminum nitride single crystal) According to the present invention, in an aluminum nitride single crystal formed on an AlN template substrate having an AlN layer formed on the surface of a sapphire substrate, voids are formed between the sapphire substrate and the aluminum nitride single crystal. The aluminum nitride single crystal contains at least one of Fe, Ni, and Co, and at least one of Mn, Cr, V, Ti, Te, Mo, Nb, Zr, Re, W, Ta, and Hf as impurity elements. The thicker the aluminum nitride single crystal formed in this case, the more likely voids are to be formed between the sapphire substrate and the aluminum nitride single crystal, so the thickness of the aluminum nitride single crystal observed as a flat plate-like portion in a cross-sectional SEM image is preferably 27 μm or more.

[0049] In order to further improve the crystal quality of the AlN single crystal produced by the manufacturing method of the present invention, it is preferable that the AlN layer of the AlN template substrate has an X-ray rocking curve half-width of 300 arcsec or less for the (10-12) plane of the C-plane AlN single crystal, and a threading dislocation density of 1×10 9 / cm 2 It is preferable that:

[0050] The above impurity elements are components of the alloy melt that are contained as impurities. The amount of impurities can be measured by SIMS analysis and is less than 1×10 15 atoms / cm 3 More than 1×10 19 atoms / cm 3 Preferably, it is 8×10 or less. 16 atoms / cm 3 More preferably, it is equal to or greater than this.

[0051] In the present invention, the aluminum nitride single crystal formed on the AlN template substrate is transparent when observed with the naked eye. The transmittance in the deep ultraviolet region is also 30 cm, for example, when the absorption coefficient α at a wavelength of 265 nm is 30 cm. -1 It is preferable that the carbon concentration of the aluminum nitride single crystal is 4×10 or less. 17It is preferable that the concentration is less than 2×10 atoms / cm. 17 atoms / cm 3 It is more preferable that the carbon concentration is equal to or less than 100 nm. This is because a low carbon concentration reduces the absorption coefficient in the ultraviolet region, and there is a high possibility that a high transmittance can be obtained.

[0052] A method for producing aluminum nitride single crystal according to an embodiment of the present invention and an apparatus applicable to the production of aluminum nitride single crystal will be described below.

[0053] [Production apparatus and method for aluminum nitride single crystals] In the examples described later, an experiment for producing aluminum nitride single crystals is carried out using an apparatus shown in FIG. 2. As shown in FIG. 2, the apparatus for producing aluminum nitride single crystals includes a reaction vessel 1, a heater 2, a heat insulator 3, a gas inlet pipe 4, a gas exhaust pipe 5, and a seed crystal holder 6. The heater 2 is provided inside the reaction vessel 1 so as to house a crucible 7 therein and cover the side of the housed crucible 7. The heater 2 is capable of heating the housed crucible 7. The heat insulator 3 is provided inside the reaction vessel 1 so as to surround the sides of the heater 2 and the crucible 7 and cover the lower part of the heater 2. The gas inlet pipe 4 is provided penetrating the ceiling of the reaction vessel 1 so as to be able to supply atmospheric gas to the inside of the reaction vessel 1. The gas exhaust pipe 5 is provided penetrating the floor of the reaction vessel 1 so as to be able to exhaust gas from inside the reaction vessel 1. The seed crystal holder 6 is provided penetrating the ceiling of the reaction vessel 1 so as to be able to slide up and down. The seed crystal holder 6 can slide up and down, so that the lower end can move back and forth between the inside and outside of a crucible 7 housed inside the heater 2 .

[0054] First, an alloy melt 8 and an AlN sintered body 9 are placed inside a crucible 7, and a seed crystal 10 is attached to the lower end of a seed crystal holder 6 or in its vicinity. When the crucible 7 is made of an AlN sintered body, the AlN sintered body 9 does not need to be placed. At this time, the seed crystal holder 6 is held in a position where the seed crystal 10 does not come into contact with the alloy melt 8. In this state, the gas inside the reaction vessel 1 is exhausted from the gas exhaust pipe 5, and the inside of the reaction vessel 1 is evacuated to a vacuum. After the evacuation, an atmospheric gas is supplied from the gas supply pipe 4, and the reaction vessel 1 is filled with the atmospheric gas.

[0055] Thereafter, electricity is applied to the heater 2 to heat the alloy melt 8 to a predetermined temperature, and Al and N are dissolved from the AlN sintered body 9 into the alloy melt 8. The alloy melt 8 is maintained at a predetermined temperature for a predetermined time until the amounts of Al and N dissolved therein reach a saturated dissolution amount and an equilibrium state is reached, thereby preparing a raw material melt. Thereafter, aluminum nitride single crystals can be manufactured by employing the following two cooling methods.

[0056] <Localized cooling method> While the temperature of the prepared raw material melt is maintained constant, the seed crystal holder 6, which is set to a temperature lower than the temperature of the raw material melt, is slid downward to bring the seed crystal 10 into contact with the surface of the raw material melt. The seed crystal 10 is held in this state, and an aluminum nitride single crystal is grown on the surface of the seed crystal 10.

[0057] <Uniform cooling method> After the raw material melt is prepared, the seed crystal holder 6 is slid downward to bring the seed crystal 10 into contact with the surface of the raw material melt. With the seed crystal 10 held in this state, the raw material melt is cooled at a predetermined rate by controlling the temperature with the heater 2, and an aluminum nitride single crystal is grown on the surface of the seed crystal 10.

[0058] In either method, after the aluminum nitride single crystal has grown, the seed crystal holder 6 is slid upward to separate the seed crystal 10 and the grown aluminum nitride single crystal from the raw material melt. After the reaction vessel 1 is cooled, the grown aluminum nitride single crystal is recovered together with the seed crystal 10.

[0059] The above-mentioned apparatus and method are merely examples. The localized cooling method and the uniform cooling method may be combined, and various modifications may be made, such as changing the manufacturing apparatus for temperature control required for single crystal growth, or adding an apparatus that enables recovery of the aluminum nitride single crystal after growth and renewal of the raw material and seed crystal. EXAMPLES

[0060] Example 1 First, an AlN template substrate was prepared. Specifically, an AlN layer was formed on a C-plane sapphire substrate (off-angle 0.11° in the M-plane direction) with a diameter of 2 inches and a thickness of 430 μm by MOCVD using trimethylaluminum (TMA) and ammonia as source gases. At this time, the growth temperature was 1613 K, the growth pressure was 13.3 mbar, and the AlN layer grown on the C-plane sapphire substrate was a C-plane AlN single crystal with a thickness of 0.5 μm. Furthermore, after the AlN single crystal was grown by the MOCVD method, it was annealed in a nitrogen atmosphere at 1873 K for 4 hours to reduce dislocations. The half-width of the X-ray rocking curve of the (10-12) plane of the C-plane AlN layer on the surface of the prepared AlN template substrate was measured, and it was 265 arcsec. Similarly, the half-width of the X-ray rocking curve of the (0002) plane of the C-plane AlN layer was measured and was 49 arcsec. In addition, the threading dislocation density measured using cross-sectional TEM images was 2×10 8 / cm 2 It was.

[0061] Referring again to the apparatus shown in FIG. 2, an aluminum nitride sintered body was used as the crucible 7, and Fe-18 mass% Cr-8 mass% Ni (SUS304L (low carbon)) was used as the alloy melt 8. In addition, N2 gas (nitrogen gas) at 1 bar was used as the atmospheric gas. In addition, an AlN template substrate prepared as described above was used as the seed crystal 10. Since an aluminum nitride sintered body was used as the crucible 7, unlike FIG. 2, an AlN sintered body 9 was not put into the crucible 7. In the experiment, the material was heated from room temperature to 1873 K over 160 minutes using Heater 2. The material was held at 1873 K for 4 hours to prepare a raw material melt in which Al and N were dissolved in a saturated state to form AlN.

[0062] After preparing the raw material melt, the seed crystal holder 6 was slid to bring the AlN template substrate into contact with the raw material melt. Then, the heating temperature of the heater 2 was adjusted to lower the temperature of the raw material melt to 1723 K over 1.25 hours at a cooling rate of 2 K / min, and an aluminum nitride single crystal was grown on the AlN layer on the surface of the AlN template substrate. After that, the seed crystal holder 6 was slid upward to separate the AlN template substrate from the melt, and the temperature was lowered to room temperature at a cooling rate of 10 K / min. During the experiment, the inside of the reaction vessel 1 was replaced with N2 gas, and then N2 gas was continuously supplied into the reaction vessel 1 at a flow rate of 0.1 L / min until the inside of the reaction vessel 1 was cooled and returned to room temperature, and the pressure inside the reaction vessel 1 was maintained at atmospheric pressure.

[0063] FIG. 3 shows a cross-sectional SEM image of the AlN template substrate after the aluminum nitride single crystal was precipitated. From FIG. 3, it was confirmed that there was an AlN single crystal with a thickness of 41 to 43 μm on the sapphire. The thickness of 43 μm shown in FIG. 3 is the value at the position where the thickness was greatest. The thickness of the grown AlN single crystal was relatively uniform. Since the thickness of the AlN layer of the AlN template substrate before growth was 0.5 μm, it was found that the aluminum nitride single crystal grew to 40.5 to 42.5 μm in 1.25 hours in this example.

[0064] In Figure 3, gaps observed as black lines were confirmed at the interface between the sapphire substrate (lower part of Figure 3) and the aluminum nitride single crystal (upper part of Figure 3), and it was found that the aluminum nitride single crystal had peeled off from the sapphire substrate, except for the part surrounded by the dashed line. In other words, it was found that there was a gap between the sapphire substrate and the aluminum nitride single crystal. From this, it is believed that peeling occurred at the interface between the AlN layer of the AlN template substrate and the sapphire substrate. If the aluminum nitride single crystal is grown thicker, the gaps observed in Figure 3 will expand, and it is expected that the aluminum nitride single crystal will peel off from the sapphire substrate.

[0065] Moreover, the AlN layer on the AlN template substrate was transparent when observed with the naked eye. The aluminum nitride single crystal in this Example 1 had a high transmittance.

[0066] In addition, the results of SIMS analysis showed that the aluminum nitride single crystal contained 1×10 Fe and 1×10 Cr. 17 atoms / cm 3 It was confirmed that the above elements were included, and that Ni was also included. Note that the AlN layer on the AlN template substrate before crystal growth did not contain these metal elements, and the carbon concentration was 4×10 17 atoms / cm 3 It is.

[0067] Example 2 In Example 2, the heater 2 was used to heat from room temperature to 1833K over 160 minutes. The temperature was held at 1833K for 4 hours to prepare a raw material melt in which Al and N were dissolved in a saturated state of AlN. After preparing the raw material melt, the seed crystal holder 6 was slid to bring the AlN template substrate into contact with the raw material melt, and the heating temperature of the heater 2 was then adjusted to lower the temperature of the raw material melt to 1783K over 0.83 hours (50 minutes) at a cooling rate of 1K / min. The aluminum nitride single crystal of Example 2 was grown under the same conditions as those of Example 1.

[0068] Example 3 In Example 3, the heater 2 was used to heat from room temperature to 1873 K over 160 minutes. The temperature was held at 1873 K for 4 hours to prepare a raw material melt in which Al and N were dissolved in a saturated state of AlN. After preparing the raw material melt, the seed crystal holder 6 was slid to bring the AlN template substrate into contact with the raw material melt, and the heating temperature of the heater 2 was then adjusted to lower the temperature of the raw material melt to 1823 K over 0.83 hours (50 minutes) at a cooling rate of 1 K / min. The aluminum nitride single crystal of Example 3 was grown under the same conditions as those of Example 1.

[0069] Cross-sectional SEM images of the AlN template substrate after the deposition of the aluminum nitride single crystal in Example 2 and Example 3 are shown in FIG. 4 and FIG. 5, respectively. From FIG. 4 and FIG. 5, it was confirmed that the AlN single crystal having a thickness of 27 μm was present on the sapphire in Example 2, and the AlN single crystal having a thickness of 32 μm was present in Example 3. The crystal growth rates, which are the values ​​obtained by dividing the thickness of the grown AlN single crystal by the time taken for the temperature to fall, were 32 μm / hour and 38 μm / hour, respectively. In each case, a gap observed as a black portion was confirmed at the interface between the sapphire substrate (lower part of the figure) and the aluminum nitride single crystal (upper part of the figure), and it was found that at least a part of the aluminum nitride single crystal had peeled off from the sapphire substrate. That is, it was found that there was a gap between the sapphire substrate and the aluminum nitride single crystal. Then, it was possible to peel off a part of the aluminum nitride single crystal from the sapphire substrate using tweezers.

[0070] Furthermore, when the half-width of the X-ray rocking curve of the (10-12) plane of the obtained aluminum nitride single crystal was confirmed, it was 331 arcsec in Example 2 and 418 arcsec in Example 3, resulting in a crystal of 450 arcsec or less. It was confirmed that the obtained aluminum nitride single crystal inherited the high-quality crystallinity of the (10-12) plane of the AlN layer of the AlN template substrate.

[0071] Comparative Example 1 As the seed crystal 10, an aluminum nitride single crystal substrate (thickness 455 μm) was used that was thin along the c-axis direction and had two surfaces that were c-planes. An aluminum nitride single crystal was grown on the surface of the seed crystal 10 in the same manner as in Example 1, except that the experiment was performed in which the seed crystal 10 was attached with its c-plane to the lower end surface of the seed crystal holder 6 so that the aluminum polar surface of the c-plane was in contact with the raw material melt.

[0072] In cross-sectional observation, no voids were observed at the expected interface between the seed crystal and the aluminum nitride single crystal grown thereon.

[0073] Moreover, when observed with the naked eye, the seed crystal was amber in color. The aluminum nitride single crystal after precipitation was also light amber in color.

[0074] Comparative Example 2 Instead of the alloy melt of Example 1, Fe-16 mass% Cr (SUS430) was used as the alloy melt 8. As the seed crystal 10, similar to Comparative Example 1, an aluminum nitride single crystal substrate (thickness 455 μm) thin along the c-axis direction and molded so that two surfaces were c-planes was used, and the seed crystal 10 was attached with its c-plane to the lower end surface of the seed crystal holder 6 so that the aluminum polar surface of the c-plane was in contact with the raw material melt. Furthermore, similar to Example 1, an aluminum nitride sintered body was used as the crucible 7, and N2 gas (nitrogen gas) was used as the atmospheric gas. In the experiment, the alloy melt 8 was heated to 1773 K by the heater 2 and held for 2 hours, and then heated to 1967 K over 9 hours. The temperature was held at 1967 K for 4 hours to prepare a raw material melt in which Al and N were dissolved in a saturated state to form AlN.

[0075] After preparing the raw material melt, the seed crystal holder 6 was slid to bring the seed crystal 10 into contact with the raw material melt, and the seed crystal holder 6 was cooled to maintain the seed crystal 10 at a temperature lower than the predetermined temperature for another 4 hours, and an aluminum nitride single crystal was grown on the surface of the seed crystal 10. The seed crystal holder 6 was then slid upward to separate it from the melt, and the temperature was then lowered to room temperature. During the experiment, the inside of the reaction vessel 1 was replaced with N2 gas, and N2 gas was continued to be supplied into the reaction vessel 1 at a flow rate of 0.1 L / min until the inside of the reaction vessel 1 was cooled and returned to room temperature, while the pressure inside the reaction vessel 1 was maintained at atmospheric pressure.

[0076] The thickness of the aluminum nitride single crystal after precipitation was 522 μm to 667 μm, and there was variation depending on the position. It was found that the aluminum nitride single crystal film grew 67 μm to 212 μm in 4 hours.

[0077] In the cross-sectional observation, no voids were found at the position expected to be the interface between the seed crystal and the aluminum nitride single crystal grown thereon.

[0078] When observed with the naked eye, the seed crystal was amber in color. The aluminum nitride single crystal after precipitation was also light amber in color.

[0079] In addition, the SIMS analysis revealed that the aluminum nitride single crystal in the precipitated region contained 7×10 Fe. 17 atoms / cm 3 and Cr is 3×10 17 atoms / cm 3 It was confirmed that the seed crystal contained Fe and Cr. The Fe and Cr in the seed crystal were below the detection limit. The carbon concentration of the seed crystal was 4×10 19 atoms / cm 3 The carbon concentration of the precipitated aluminum nitride single crystal was as high as 6×10 17 atoms / cm 3 It was.

[0080] Comparative Example 3 As the alloy melt 8, Ni-20 mol% Al alloy was used, and the Ni-20 mol% Al alloy was placed in a crucible 7 made of an aluminum nitride sintered body. After evacuating the inside of the reaction vessel, N2 gas was supplied from a gas supply pipe to replace the inside of the reaction vessel with N2, and the reaction vessel was made into an N2 gas atmosphere of 1 bar. As the seed crystal 10, an AlN template substrate similar to that in Example 1 was used, and this template substrate was placed on the side of a seed crystal holder 6 having a double tube structure equipped with a cooling mechanism. Next, while holding the seed crystal holder made of a double tube holding the AlN template substrate so as not to come into contact with the raw material melt, the heater 2 made of a high-frequency coil was energized to heat the susceptor, thereby heating the raw material melt until the temperature of the interface between the crucible 7 and the raw material melt reached 1852K. Then, while cooling the inner tube of the seed crystal holder by introducing Ar gas as a cooling gas at a flow rate of 10 L / min, the seed crystal holder 6 was immersed in the raw material melt, and was held for 7 hours while maintaining the temperature of the high-temperature part in the melt and making the periphery of the holder in the melt a low-temperature part, thereby precipitating an aluminum nitride single crystal on the AlN template substrate. Thereafter, the holder was pulled out of the raw material melt and cooled to room temperature.

[0081] In Comparative Example 3, the aluminum nitride single crystal grew to only 3.7 μm in 7 hours, which was a slower crystal growth rate than in Example 1. In addition, no voids were observed at the interface between the sapphire substrate and the aluminum nitride single crystal grown thereon.

[0082] From the above results, it is evident that, according to this embodiment, by applying the manufacturing method of the present invention, it is possible to manufacture thick aluminum nitride single crystal having a thickness of 30 μm or more in a short period of time, and it is also possible to easily provide transparent aluminum nitride single crystal which has voids at the interface with the sapphire substrate. [Industrial Applicability]

[0083] According to the present invention, it is possible to produce a thick aluminum nitride single crystal having a high crystal growth rate, and it is also possible to easily provide a transparent aluminum nitride single crystal which can be easily peeled off from a sapphire substrate. [Explanation of symbols]

[0084] 1 Reaction vessel 2 Heater 3. Insulation 4 Gas supply pipe 5 Gas exhaust pipe 6 Seed Crystal Holder 7 Crucible 8 Joint financial liquid 9. AlN sintered body 10 seed crystals

Claims

1. A step of preparing a raw material melt by dissolving Al and N in an aluminum nitride saturated state in an alloy melt composed of at least one element selected from the group consisting of Fe, Ni, and Co, and at least one element selected from the group consisting of Mn, Cr, V, Ti, Te, Mo, Nb, Zr, Re, W, Ta, and Hf at a predetermined temperature; bringing an AlN template substrate, which comprises a sapphire substrate having an AlN layer formed on its surface, into contact with the raw material melt and cooling at least the periphery of the AlN template substrate to a temperature lower than the predetermined temperature, thereby growing an aluminum nitride single crystal on the AlN layer side of the AlN template substrate; the AlN layer of the AlN template substrate has an X-ray rocking curve half-width of 300 arcsec or less for a (10-12) plane of a C-plane AlN single crystal; a void is formed between the sapphire substrate and the aluminum nitride single crystal after the aluminum nitride single crystal is grown.

2. 2. The method for producing an aluminum nitride single crystal according to claim 1, wherein the alloy melt is an Fe--Cr alloy melt or an Fe--Cr--Ni alloy melt.

3. 2. The method for producing an aluminum nitride single crystal according to claim 1, further comprising the step of peeling off the aluminum nitride single crystal from the sapphire substrate after growing the aluminum nitride single crystal.

4. 2. The method for producing an aluminum nitride single crystal according to claim 1, wherein the alloy melt is brought into contact with a substance containing aluminum nitride, and the alloy melt is held at the predetermined temperature for a predetermined time so that Al and N dissolve from the substance into the alloy melt and aluminum nitride is saturated at the predetermined temperature, and then the AlN template substrate is brought into contact with the raw material melt.

5. An aluminum nitride single crystal formed on an AlN template substrate having an AlN layer formed on a surface of a sapphire substrate, the AlN layer of the AlN template substrate has an X-ray rocking curve half-width of 300 arcsec or less for a (10-12) plane of a C-plane AlN single crystal; a gap is formed between the sapphire substrate and the aluminum nitride single crystal, At least one element selected from the group consisting of Fe, Ni, and Co; An aluminum nitride single crystal containing at least one of Mn, Cr, V, Ti, Te, Mo, Nb, Zr, Re, W, Ta and Hf as an impurity element.

6. An aluminum nitride single crystal formed on an AlN template substrate having an AlN layer formed on a surface of a sapphire substrate, The AlN layer of the AlN template substrate has a threading dislocation density of 1×10 9 / cm 2 is as follows: a gap is formed between the sapphire substrate and the aluminum nitride single crystal, At least one element selected from the group consisting of Fe, Ni, and Co; An aluminum nitride single crystal containing at least one of Mn, Cr, V, Ti, Te, Mo, Nb, Zr, Re, W, Ta and Hf as an impurity element.

Citation Information

Patent Citations

  • Process for preparing aln single crystal

    JP2003335600A

  • Production method for aln single crystal

    JP2006306638A

  • Production method of aluminum nitride crystal

    JP2019194133A

  • JP2022

  • Method for manufacturing aluminum nitride crystal

    JP2022037713A